2017
DOI: 10.1016/j.bandc.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual language intrusions and other speech errors in Alzheimer’s disease

Abstract: The current study investigated how Alzheimer’s disease (AD) affects production of speech errors in reading-aloud. Twelve Spanish-English bilinguals with AD and 19 matched controls read-aloud 8 paragraphs in four conditions (a) English-only, (b) Spanish-only, (c) English-mixed (mostly English with 6 Spanish words), and (d) Spanish-mixed (mostly Spanish with 6 English words). Reading elicited language intrusions (e.g., saying la instead of the), and several types of within-language errors (e.g., saying their ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 104 publications
5
46
1
Order By: Relevance
“…Reversed dominance effects. In previous studies (Gollan & Goldrick, 2016Gollan, Schotter, et al, 2014;Gollan et al, 2017;Li & Gollan, 2018;Ratiu & Azuma, 2017), bilinguals more often mistakenly replaced a word written in the dominant language with its nondominant languagetranslation equivalent than the opposite, an effect we refer to as reversed dominance. We replicated this pattern; Chinesedominant bilinguals were more likely to produce English intrusions, saying the English translation instead of the written Chinese word, than vice versa.…”
Section: Error Production Measuresmentioning
confidence: 86%
See 1 more Smart Citation
“…Reversed dominance effects. In previous studies (Gollan & Goldrick, 2016Gollan, Schotter, et al, 2014;Gollan et al, 2017;Li & Gollan, 2018;Ratiu & Azuma, 2017), bilinguals more often mistakenly replaced a word written in the dominant language with its nondominant languagetranslation equivalent than the opposite, an effect we refer to as reversed dominance. We replicated this pattern; Chinesedominant bilinguals were more likely to produce English intrusions, saying the English translation instead of the written Chinese word, than vice versa.…”
Section: Error Production Measuresmentioning
confidence: 86%
“…Bilinguals produce language intrusion errors systematically when reading aloud mixed-language paragraphs, and these errors follow similar patterns as spontaneously occurring intrusions. For example, similar to intrusion errors produced in spontaneous speech (Poulisse & Bongaerts, 1994), intrusions produced in the read-aloud task are more common for function words than content words (e.g., saying pero when the written word was but; Gollan & Goldrick, 2016Gollan, Schotter, Gomez, Murillo, & Rayner, 2014;Gollan, Stasenko, Li, & Salmon, 2017;Kolers, 1966;Ratiu & Azuma, 2017). This similarity suggests the source of the errors in the read-aloud task is similar to the source in spontaneous speech (i.e., a failure in speech planning and/or monitoring; Gollan & Goldrick, 2016;Gollan, Schotter, et al, 2014) rather than a source specific to reading (i.e., a failure to allocate attention to to-be-said words when reading that would lead to misperception errors; Goodman & Goodman, 1977).…”
mentioning
confidence: 91%
“…Exceptions Prior research has shown that a reversed language dominance effect can occur during bilingual language production in mixed language blocks with an unpredictable (e.g., Costa, Santesteban, & Ivanova, 2006;Li & Gollan, 2018) and predictable language sequence (e.g., Declerck, Stephan, Koch, & Philipp, 2015;Declerck et al, 2013), and during reading aloud of written paragraphs (e.g., Gollan & Goldrick, 2016Gollan, Schotter, Gomez, Murillo, & Rayner, 2014;Gollan, Stasenko, Li, & Salmon, 2017), picture naming with sentences (Tarlowski, Wodniecka, & Marzecová, 2012), and picture/digit naming with single words (e.g., Costa & Santesteban, 2004;Heikoop et al, 2016). However, while the reversed language dominance effect can occur in most contexts, the effect does not always occur.…”
Section: Markers Of Proactive Language Controlmentioning
confidence: 99%
“…For example, when reading a sentence like: The curious thing is that very poca people spoke negatively about her, Spanish-English bilinguals might produce, The curious thing is that very few people spoke negatively about her instead (i.e., mistakenly producing the English translation of the word poca). Previous work using the read-aloud task revealed language control to be constrained by language dominance; when Spanish-English bilinguals read mixed-language paragraphs, most of the cross-language intrusion errors they produced involved dominant language targets embedded in paragraphs written primarily in the nondominant language (i.e., a reversed dominance effect; Gollan & Goldrick, 2016Gollan, Schotter, Gomez, Murillo, & Rayner, 2014;Gollan, Stasenko, Li, & Salmon, 2017). Syntactic factors also influence language control; switches that violated grammatical constraints on code-switched speech elicited more intrusions (Gollan & Goldrick, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, default language selection exerted a powerful influence on intrusion errors; switches out of the default language elicited the majority of errors while switches back rarely induced errors (Gollan & Goldrick, 2018) even in bilinguals with Alzheimer's disease (see Fig. 1 in Gollan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%